The Quranic Principle of Wasatiyyah as the Foundation of Malaysia Madani’s Civilizational Framework (International Journal of World Civilizations and Philosophical Studies, 2025)
This study explores wasatiyyah as a civilizational framework within Malaysia Madani, analyzing its Quranic foundations and practical application in contemporary society. The objective is to investigate how wasatiyyah, which emphasizes moderation, balance, and justice, can guide Malaysia’s development while promoting social harmony, ethical governance, and inclusive growth. Using a qualitative approach, the research involves a literature review and content analysis of Quranic verses, Islamic scholarship, and Malaysian policies related to Malaysia Madani. The findings reveal that wasatiyyah offers a holistic model for balancing traditional values with modern advancements. It advocates for fairness, justice, and avoidance of extremes, making it highly relevant for fostering a just and prosperous society. The study suggests that by embedding these principles into national policies, Malaysia can achieve sustainable development that prioritizes both social well-being and development progress. The application of wasatiyyah in Malaysia Madani can create a society that harmonizes spiritual values with global progress, fostering peace, unity, and moral integrity in governance and everyday life.